Improvement of salinity tolerance of citrus scion using tolerant rootstocks and interstocks - Shafieizargar, Alireza (2014)
Soil salinity is one of the most serious environmental threats, that extremely restricts crop production. One of the most effective strategies to overcome salinity effects is by growing salt tolerance plant species. Citrus is a commercial fruit crop and grown exclusively in tropical and sub-tropical zones. It is a glycophyte. The objective of this study was to evaluate the responses of citrus to salinity stress and to estimate amelioration of salinity effects by using tolerant rootstocks, diploid and tetraploid interstocks. Salinity tolerance of five citrus rootstocks namely Cleopatra mandarin (Citrus reshni Hort. Ex Tan.), Carrizo citrange [(Citrus sinensis (L.) Osbeck×Ponicrus trifoliate (L.) Raf.], Tiwanica (Citrus taiwanica Tan.& Shimada), Bacraii (Citrus limettioides × Citrus reticulate) and Shaker [(Citrus limettioides × Citrus reticulate)× Citrus reshni] during germination was tested at various NaCl concentrations. Salt stress affected seed germination, emergence spread, percentage of final emergence and percentage of seedlings survival. At germination stage, Cleopatra mandarin exhibited higher salt-tolerance than other species. In the subsequent study, the growth parameters, mineral concentration, physiological and biochemical traits of abovementioned citrus species were studied to estimate the degree of salt tolerance. The results indicated that the lowest Na and Cl concentrations were observed in leaves of Shaker rootstock. Also results obtained showed that Shaker and Cleopatra mandarin rootstocks maintained higher RWC and proline content. To allow the testing of resistant rootstock, a salt sensitive scion cultivar is needed. For this purpose, salt sensitivity assessment of two locally available citrus cultivars,Limau Nipis (Citrus aurantifolia Swingle) and Limau Kesturi (Citrus microcarpa Bunge) were subjected to NaCl salinity. The results demonstrated that cv. Limau Kesturi was more sensitive to salt stress than cv. Limau Nipis. Therefore, cv. Limau Kesturi was used as a salinity susceptible cultivar in combination with citrus rootstocks for further experimentation in determination of suitable rootstock that could induce salt resistance of the scion. Evaluation of the level of salt tolerance of Limau Kesturi plants budded on Cleopatra mandarin and Shaker rootstocks revealed that salt stress decreased leaf N, P, K concentrations and RWC, while Na, Cl,proline, MDA and H2O2 concentrations of budded Limau Kesturi increased on both tested rootstocks. The results suggested that the Shaker exhibited higher tolerance to salt stress than the Cleopatra mandarin and therefore can be used as an appropriate rootstock. Based on the changes in leaf mineral contents and biochemical compositions in response of tetraploid and diploid Dez orange cultivars (Citrus sinensis (L.) Osbeck grown under saline condition, we noticed that tetraploid Dez orange had induced a higher level of salt tolerance in comparison to diploid Dez orange. Use of tetraploid Dez oranges as interstock for Limau Kesturi showed the tetraploid cultivar generate more tolerance plants against NaCl salt stress and the plant was able to keep acceptable concentrations of mineral contents, proline, MDA and H2O2. Overall, evidences recorded from this study proved that among the rootstocks tested,Shaker, and tetraploid interstocked plants are more tolerant to salinity stress and therefore can be introduced as new source of plant materials for salinity tolerance in the citrus industry.